(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This paper, interrogates the persistent paradox of “surplus amidst scarcity” in contemporary India, where record food grain stocks coexist with widespread malnutrition. Moving beyond the traditional production-centric paradigm rooted in Malthusian concerns, the study reconceptualizes food security as a dynamic political process shaped by power relations among the state, agrarian classes, and corporate actors. Building upon Amartya Sen’s Entitlement Approach, the paper advances a multi-theoretical framework integrating Food Regime Theory, the Agrarian Question, and New Institutional Economics to explain the divergence between aggregate availability and individual access. The analysis traces the evolution of India’s food policy from the Green Revolution’s productivist model to the rights-based framework of the National Food Security Act (2013), and further to the contemporary phase of digital welfare characterized by biometric governance and direct benefit transfers. It argues that the current regime reflects a shift from “bureaucratic entitlements” to “algorithmic entitlements,” raising concerns about exclusion, accountability, and the redefinition of citizenship. By examining class dynamics, federal tensions, and the growing corporatization of food systems, the paper highlights how competing interests produce a dual food economy—state-supported subsistence for the poor and market-driven nutrition for the affluent. The study further introduces the concept of “nutritional sovereignty,” emphasizing the need to move beyond caloric sufficiency toward diversified, ecologically sustainable, and nutritionally adequate food systems. The paper concludes that food security in India must be understood as a question of democratic governance rather than mere policy delivery. It calls for a transition toward a decentralized, inclusive, and climate-resilient “food democracy” that restores agency to citizens while addressing structural inequalities in access and distribution.